Remarks on the Subject of Back-Up Protection of Residual Current Devices - Czapp, Stanislaw; Kowalak, Daniel (The International Conference on Information and Digital Technologies (Online), 2019)
Residual current devices without integral overcurrent protection (RCCBs) are back-up protected by fuses or miniature circuit-breakers (MCBs). If the latter are used, special attention must be given to the coordination between an RCCB and an MCB. This paper indicates probable cases of the aforementioned devices coordination, in which back-up protection of the RCCB is not adequate. A laboratory test has shown that depending on the used type of the MCB, in case of value of short-circuit current close to the making and breaking capacity of an RCCB, excessive arc stress of the RCCB may occur. In case of short-circuit current of value close to the rated conditional short-circuit current of the RCCB, permissible values of peak current and Joule integral for the RCCB may be exceeded. All these stresses may limit electrical endurance of RCCBs.